(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In recent years, researchers have looked at the discovery of new alternative sources of antimicrobial agents, especially from plant sources. Camellia sinensis has served humanity as the source of medicinal agents from the very beginning. Phytochemical agents present in the leaves to mark the compounds responsible for the antimicrobial activity. Phytochemical screening of plant leaves reveals the presence of saponin, alkaloids, flavonoids, steroids, phenols, tannins and glycosides. Various leaf extracts of camelia sinensis were prepared and their antimicrobial activity was evaluated against the Gram-positive and gram negative bacterial strains if disc-diffusion method was done. Antimicrobial activity of many extracts of camelia sinensis leaves was created in an attempt to develop a new drug drug of natural origin for the treatment of pathogenic microbes.